Comparison between calibrate and non-calibrate manning ‘N’ value for flood inundation mapping / Muhammad Haziq Rossman - Rossman, Muhammad Haziq (2020)
In the years 2010, the heavy flood are hit two state which is Kedah and Perlis cause form heavy rainfall occur October until December. Padang Terap, Kedah was chose as thedominion research because that area are affected worth cause heavy flood duringNovember 2010. The aim of this study is (1) To generate flood inundation mapping using DEM data for calibrated and non-calibrated data, (2)To compare the flood depth betweenmanning ‘n’ value for calibrated and non-calibrated flood inundation mapping and (3)Tovalidate calibrated and non-calibrated manning ‘n’ value flood inundation mapping withground truth data. HEC-GeoRAS is the software are used to perform river analysis.Steady flow that perform on HECRAS software to generate flood inundation by certainparameter that used which is channel and flood plain of manning ‘n’ value. Five intervalcross section which is 100m 200m 300m 400m and 500m running for each calibrate andnon-calibrate flood inundation mapping. The result indicated the flood inundationmapping for each five cross section base discharge and manning ‘n’ value. Water Surface Elevation elaborated by comparison observation and predicted result. RMSE and MAE result for validated the flood depth calibrate and non-calibrate flood inundation mapping. Comparison flood area coverage between predicted by model and ground truth data. Theresult of this study will benefit by provide real able and meaningful information relate toflood.